Improving Educational Quality Through the PPEPP Cycle in the Internal Quality Assurance System: A Case Study of Al Banna Middle School, Denpasar, Bali - Asrina Astagani; Khoirul Anwar (Civiliza Publishing, Indonesia., 2026)
Improving the quality of education is a strategic demand for educational units in facing scientific developments, social change, and global competition. The Internal Quality Assurance System (SPMI) through the Determination, Implementation, Evaluation, Control, and Improvement (PPEPP) cycle is an important instrument to ensure continuous quality improvement. This study aims to analyze the implementation of the PPEPP cycle in improving the quality of education at SMP Al Banna Denpasar Bali. This research method uses a qualitative approach with a case study design based on document analysis. Data were obtained from school profile documents, quality mapping, quality improvement program plans and implementation, internal quality evaluation and audit reports, and quality standard setting documents. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of PPEPP was carried out systematically through quality mapping based on eight National Education Standards, the preparation of quality improvement programs, the implementation of human resource strengthening programs, the development of an integrated curriculum, and periodic internal quality evaluation and audits. The implementation of the PPEPP cycle has contributed to improving the quality of education, as demonstrated by improved school governance, a strengthened culture of quality, and a 47.27% increase in student enrollment from 275 in the 2020/2021 academic year to 405 in the 2025/2026 academic year. These findings demonstrate that the PPEPP cycle serves as a strategic instrument for achieving systematic, measurable, and sustainable improvements in education quality.